Development of encapsulated air microparticles using spray drying and sessile single droplet drying - Tengku Farizan Izzi Che Ku Jusoh
The aim of this research was to produce spray dried particles with one large vacuole and controlled surface wettability, also known as encapsulated air microparticles, to be potentially applied as the dispersed gas phase in foambased processed foods. Droplets containing a mixture of the slightly hydrophobic and thus surface active gum Arabic (GA) and the hydrophilic maltodextrin (MD) was selected for the development of encapsulated air microparticles based on literature reports of hollow spray dried particles": 2. A sessile single droplet drying (SDD) on a hydrophobic surface and spray drying with a two-fluid atomiser were employed to evaluate the impact of droplet compositions (ratio of GA:MD, solids concentration and DE-value of MD) and processing conditions (drying temperature and droplet size) on the particle formation and the wetting properties of the particles. The sessile SDD study revealed that the mechanical strength of the skin and the drying rate were the key determining factors for the development of particles with one large vacuole. These particles were also haracterised by a smooth surface appearance. The formation of one large vacuole (and a smooth surface) required the droplet to withstand surface collapse during drying. These conditions were fulfilled for droplets containing a higher proportion of GA than MD, for a higher solids concentration (40% w/v) and for the MD with the lowest dextrose equivalent (DE 7) of two MDs included in this research. A high drying rate constant at higher drying temperature (120 "C) and smaller initial droplet volume (1 1-11) resulted in an earlier onset of bubble nucleation, and thus were more likely to lead to the formation of a large vacuole. Particle morphologies produced by spray drying were comparable to those produced in the SDD experiments. The highest fraction of smooth-surface hollow particles (15%) was achieved by spray drying the feed that contained high solids (40% w/v) at high inlet temperature (220°C) and slow feed rate (300 ml/h), whereas the opposite conditions resulted in the lowest percentage of hollow particles (2%). The wetting behaviour of spray dried powders was found to be identical to SOD particles, wherein particles higher in GA showed poorer wetting (by water) due to the enrichment of the more hydrophobic GA at the surface of the particles. Likewise, the dissolution time increased with an increasing amount of GA in the particles due to the ability to hold higher amount of water (swelling) before the onset of collapse. The increasing dissolution time is advantageous in certain applications such as ice cream manufacture. Overall, this research has provided insight into fundamental aspects of encapsulated air microparticles, whereby GA has demonstrated convincing encapsulating material for the development of hollow particles, as well as in the control of particle wettability. The re-design SOD set-up developed in this research can be used as a design tool to achieve specific particle morphology and thus particle functionality for processing using spray drying.